2012
DOI: 10.1016/j.bbamcr.2011.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Multitasking in the mitochondrion by the ATP-dependent Lon protease

Abstract: The AAA+ Lon protease is a soluble single-ringed homo-oligomer, which represents the most streamlined operational unit mediating ATP-dependent proteolysis. Despite its simplicity, the architecture of Lon proteases exhibits a species-specific diversity. Homology modeling provides insights into the structural features that distinguish bacterial and human Lon proteases as hexameric complexes from yeast Lon, which is uniquely heptameric. The best-understood functions of mitochondrial Lon are linked to maintaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
140
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(142 citation statements)
references
References 133 publications
1
140
0
1
Order By: Relevance
“…This AAA + protease is involved in mitochondrial protein quality control. It degrades misfolded or oxidized proteins and acts as a chaperone in the assembly of protein complexes (56). We confirmed that LonP1 is induced under lipotoxic conditions in rat b-cells ( Supplementary Fig.…”
Section: Mitochondrial Dynamics and Quality Controlsupporting
confidence: 69%
“…This AAA + protease is involved in mitochondrial protein quality control. It degrades misfolded or oxidized proteins and acts as a chaperone in the assembly of protein complexes (56). We confirmed that LonP1 is induced under lipotoxic conditions in rat b-cells ( Supplementary Fig.…”
Section: Mitochondrial Dynamics and Quality Controlsupporting
confidence: 69%
“…It has been suggested that Lon could be a viable anticancer drug target as drugs that inhibit Lon activity lead to cancer cell apoptosis in vitro either due to uncontrolled accumulation of misfolded proteins in general or due to the failure to control a specific regulator (48,51,52). General inhibitors of Lon activity, however, could cause potentially problematic pleiotropic side effects, and Lon defects have been associated with poor mitochondrial health and multiple human diseases (47,53,54). Thus, specific inhibitors that block proteolysis of key oncogenic substrates would be preferable and the SmiA precedent offers the potential for pathwayspecific antiadaptor therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…Eukaryotic Lon (37% identical to LonA of B. subtilis) (SI Appendix, Fig. S7) is involved in both the general degradation of misfolded proteins and in the specific remodeling of the mitochondrial proteins cytochrome C oxidase COX4-1, transcription factor A (TFAM), and the cholesterol regulator StAR (47)(48)(49)(50). It has been suggested that Lon could be a viable anticancer drug target as drugs that inhibit Lon activity lead to cancer cell apoptosis in vitro either due to uncontrolled accumulation of misfolded proteins in general or due to the failure to control a specific regulator (48,51,52).…”
Section: Discussionmentioning
confidence: 99%
“…6 The ATP-dependent Lon protease is highly conserved from bacteria (La protease) to mammalian mitochondria and peroxisomes, and operates in protein quality control and stress response pathways by selectively degrading misfolded, misassembled, or damaged proteins. 7,8 Mitochondrial Lon supports cell viability during hypoxic, proteotoxic, and endoplasmic reticulum (ER) stress, [9][10][11] which are common stress phenotypes of cancer cells. During hypoxia, Lon is up-regulated by the hypoxia inducible factor-1␣ (HIF1-␣).…”
Section: Introductionmentioning
confidence: 99%